Consumer demand analysis for electric cars in Russia and recommendations development for its increase - D. A. Rusanov (Вестник университета)
The global trend among nations at this moment in time is to preserve nature, abandon fossil energy resources, and strive for carbon neutrality. One of the key links in creating a beautiful future world without dangerous emissions into the atmosphere is vehicles electrification and transition from traditional internal combustion engine to electric propulsion systems. Russia is following agreements with other countries and is trying to reorient itself towards electric cars development. However, the share of such transportation cannot yet compete in any way with the conventional internal combustion engine. Statistical information on the use of electric cars has been studied, which reflects the current situation of this segment of the transportation sector of the economy in various countries of the world. A comparative analysis of the opinions of potential consumers in the Russian and Western mobility vehicles markets based on data taken from open sources has been carried out. Important factors that are essential for consumers in the Russian market have been considered, and measures that can be taken to stimulate demand in this segment have been proposed. The findings can be used to implement  government projects  to increase consumer  demand for economy-class electric cars on the Russian market.